2006
DOI: 10.1159/000096068
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Matrix-Related Molecules in the Development of Chronic Thy1.1 Nephritis

Abstract: Background/Aim: Matrix production and degradation are critically important in chronic nephritis. Our aim was to investigate the precise expression of matrix-related molecules which is essential for understanding the pathogenesis of renal disease. Methods: Chronic nephritis was induced by a single injection of anti-Thy1.1 antibody to unilaterally nephrectomized rats. RNA was extracted from renal cortex and isolated glomeruli 4, 7, and 10 weeks after the antibody injection. Matrix-related gene expressions were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…Therefore, damage of the GBM and GECs leads to an increase in proteinuria. We have previously reported sustained proteinuria in chronic anti-Thy1.1 nephritic rats, associated with a decreased number of ACSs on the GBM, an abnormal remodeling of type IV collagen in the GBM, and predominant injury in GECs [16,27]. The present study demonstrates that the treatment with the MMP inhibitor compound A prevented the loss of ACSs on the GBM.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Therefore, damage of the GBM and GECs leads to an increase in proteinuria. We have previously reported sustained proteinuria in chronic anti-Thy1.1 nephritic rats, associated with a decreased number of ACSs on the GBM, an abnormal remodeling of type IV collagen in the GBM, and predominant injury in GECs [16,27]. The present study demonstrates that the treatment with the MMP inhibitor compound A prevented the loss of ACSs on the GBM.…”
Section: Discussionsupporting
confidence: 63%
“…It has been reported that MMP−2 contributes to the process of phenotype changes in MCs and TECs [10,11,15]. We have previously demonstrated that MMP−2 activity is enhanced in anti-Thy1.1 nephritis [16]. Compound A obviously suppressed ECM deposition with decreased gene expressions of TGF-β1 as well as α1(I), α1(III), and α1(IV) collagen in the renal cortex.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations